Mitigating The Long-Term Risks of Debt and Consumerism Behaviour: In The Perspective of Gen Z in Indonesia and Malaysia - Widayati , Catur; Hariani , Swarmilah; Budiharjo , Roy; Omar , Rusdi; Fakhrorazi , A.; Khamis , Kamarul Azman (Journal of Ecohumanism, 2024)
The purpose of this study is to create regulations, ethical standards for the use of BNPL that play an important role in protecting consumers. The population of this study is students at universities in Indonesia and Malaysia, with a sample of 410 respondents used. This study uses a quantitative approach with a survey, data will be collected from students who shop online in Indonesia and Malaysia. The test results of this study show that: (1) BNPL Service Convenience has a significant positive effect on Intention to Use BNPL in students who shop online in Indonesia and Malaysia; (2) Impulse Buying has a significant positive effect on Intention to Use BNPL in students who shop online in Indonesia and Malaysia; (3) Intention to Use BNPL has a significant positive effect on BNPL User Behavior in students who shop online in Indonesia and Malaysia; (4) Financial Self-control moderates pseudo-the influence of Intention to Use BNPL on BNPL User Behavior; (5) Psychological Risk pseudo-moderates the effect of Intention to Use BNPL on BNPL User Behavior. The implications of this study underscore the importance of designing more proactive policies in mitigating long-term risks from consumer debt and consumerism among Gen Z in Indonesia and Malaysia. Considering the high use of the Buy Now Pay Later (BNPL) scheme among the younger generation, the policies formulated should include more in-depth financial literacy education, regulations that protect consumers from excessive debt accumulation, and policy frameworks that promote more sustainable consumption behaviors.